Case reportsSuspicion of Behçet’s disease – case report - Jakubowicz, Oliwia; Żaba, Ryszard; Czarnecka-Operacz, Magdalena; Silny, Wojciech (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2009)
Behçet’s disease is a chronic, multi-systemic disease, characterized by relapsing ulceration of the mucous membrane of the oral cavity and genitals, and very often eye disorders are among the leading manifestations. Aetiology of the disease is not known, with genetic, environmental and also infectious factors taken into consideration. Though clinical cases are found all over the world, it is mostly diagnosed in Mediterranean countries and along the old commercial Silk Road (East Asia, China, Korea, Japan). First signs and symptoms of the disease appear at the age of 20-35 years. Presence of HLA-B51, male gender and early onset of systemic symptoms worsen the prognosis. Diagnostic criteria of the disease proposed by the International Study Group for Behçet’s disease in 1990 include main criteria and 4 additional ones. Because of the low prevalence rate of the disease in our geographical region and also due to the unspecific clinical appearance the disease presents significant diagnostic and therapeutic problems. This paper presents a 39-year old patient suffering from chronic ophthalmological clinical problems since early childhood and suspicion of Behçet’s disease.